2013
DOI: 10.1002/pola.26884
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-ene polymerizations using imide-based monomers

Abstract: New diene and dithiol monomers, based on aromatic imides such as benzophenone‐3,3′,4,4′‐tetracarboxylic diimide were synthesized and used in thiol‐ene polymerizations which yield poly(imide‐co‐thioether)s. These linear polymers exhibit limited solubility in various organic solvents. The molecular weights of the polymers were found to decrease with increasing imide content. The glass transition temperature (Tg) of these polymers is dependent on imide content, with Tg values ranging from −55 °C (with no imide) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Using thiol-ene polymerization containing imide groups, Shipp et al showed a maximum T g of 13 °C with diallyl bisphenone imide and ethylene glycol dithiol monomers, but with no report of mechanical properties; Zhang et al produced a crosslinked thiol-ene polymer from bis maleimide and trimethylolpropane tris(3-mercaptopropionate) (TMPMP) thiol monomers, showing broad T g 's in the range of 40-90 °C and tensile strength up to 23 MPa. 41,42 To fully understand the potential application in electronic substrates, we conduct a thorough investigation of the material property space of bisimidebased thiol-ene polymers. We aim to synthesize glassy network polymers with high T g 's, high tensile strength, high resistance to thermal decomposition, and favorable electrical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Using thiol-ene polymerization containing imide groups, Shipp et al showed a maximum T g of 13 °C with diallyl bisphenone imide and ethylene glycol dithiol monomers, but with no report of mechanical properties; Zhang et al produced a crosslinked thiol-ene polymer from bis maleimide and trimethylolpropane tris(3-mercaptopropionate) (TMPMP) thiol monomers, showing broad T g 's in the range of 40-90 °C and tensile strength up to 23 MPa. 41,42 To fully understand the potential application in electronic substrates, we conduct a thorough investigation of the material property space of bisimidebased thiol-ene polymers. We aim to synthesize glassy network polymers with high T g 's, high tensile strength, high resistance to thermal decomposition, and favorable electrical properties.…”
Section: Resultsmentioning
confidence: 99%
“…The main disadvantage of free-radical photopolymerization is the poor control of molecular weight and its distribution [ 36 ], as well as oxygen inhibition [ 37 ]. Thiol-Michael photopolymerization is a light activated reaction [ 38 ] which proceeds rapidly with no side products [ 39 ]. Its main advantages over free-radical photopolymerization are no inhibition by moisture and oxygen [ 40 ] and generation of homogenous materials [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the synthesis of this important group of molecules is still associated with time-consuming and complicated protocols oen leading to contaminated products in low yields. [17][18][19] In addition, purication of these molecules is usually very difficult because of their generally low solubility and tendency to form undened polymeric materials. For these reasons, the development of an accessible methodology based on microwave-assisted synthesis of non-NDI/PBI diimides in short reaction times, with easy work up and in high yields is greatly desirable from the viewpoints of both synthesis and the application potential of these molecules.…”
Section: -14mentioning
confidence: 99%